Wireless smart health monitoring system via mobile phone - Bakar, Nur Hidayah Binti Abu; Abdullah, Khaizuran; Islam, Md. Rafiqul (IEEE, 2016)
Health monitoring system offers a lot of benefits to people life especially for those who have chronic disease and need daily observation. This health monitoring system will improve quality of life. Information technology (IT) and wireless communication system has the potential to improve safety,quality and efficiency of health care. By this improvement of the technology, doctors and patients can easily access and use health information as needed. In this research, health monitoring system, doctors and patients can use it in order to monitor and check their condition via mobile phone. The patients can be alerted if they are required to do the treatment or not. Arduiono Uno and GSM together with temperature and pulse rate sensors are used for this research. Our results is correct since, the number of older people becomes larger for abnormal patient’s condition.